Freedom of religion: UN and European human rights law and practice - Taylor, Paul M (Cambridge University, 2013)
Freedom of thought, conscience and religion is one of the core freedoms found in international human rights instruments at both UN and European level. This timely study is the first to provide a detailed critique of the standards applicable to freedom of religion within both the UN and Europe.